The Dark Figure of Online Property Crime: Is Cyberspace Hiding a Crime Wave?. (28th July 2016) - Tcherni, M.; Davies, A.; Lopes, G.; Lizotte, A.
Abstract : A pronounced drop in crime, since the early 1990s, has encompassed every crime category tracked by the FBI's Uniform Crime Reports, including property crime. However, over the same period, the rates of online property crime (OPC) have been on the rise according to available evidence. We delineate the extent of our knowledge and data concerning cybercrime and identity theft and, using data from several nationally representative victimization surveys, offer an alternative view of property crime trends while pointing out the glaring gap in crime reporting and accounting in relation to the growing category of property crimes perpetrated online. In addition, we compare estimated costs of traditional property crime vs. OPC. Finally, we identify the main challenges for obtaining reliable data on OPC and discuss their implications, especially when applying the traditional methods of compiling crime statistics.